Academic Supervision and Principal’s Leadership Influence on Teacher’s Performance During a Pandemic - Purwati, Lilik; Ahyani, Nur; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2022)
Academic supervision is a type of self-evaluation used to maximize educational implementation, which is also supported by the leadership of competent school principals. As a result, the purpose of this study was to describe the impact of academic supervision and principal’s leadership on teacher performance. This study's execution is based on quantitative research methodologies. The data was examined proportionately using data from surveys, observations, and documents. The study's findings revealed a positive and significant effect of academic supervision on teacher performance; a positive and significant influence of principal leadership on teacher performance; and, in simultaneous testing, a positive and significant effect of academic supervision and principal leadership combined on teacher performance during the pandemic at SD Negeri Madang Suku III District. The effect of the two independent factors on the dependent variable is categorized as modest.